FAKTOR RESIKO KEJADIAN DIABETES MELITUS TIPE 2 DI PUSKESMAS PURWOKERTO SELATAN KABUPATEN BANYUMAS - Fasikhatul Qomariyah; Peppy Octaviani DM; Rani Prabandari (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Diabetes Mellitus (DM) type 2 is a metabolic disease characterized by an increase in blood sugar levels caused by a decrease in insulin secretion or insulin function disorders.. The purpose of this study was to determine the risk factors for type 2 diabetes melitus based on age, gender, obesity, physical activity, smoking habits in the South Purwokerto Public Health Center, Banyumas Regency. The method used is quqntitative prospectively using a correlation description design or design with a cross sectional approach. The results of this study using the charactristics of the respondents showed that of the 64 patients the majority of the respondents were aged in the adult category (20-60 years) as many as 34 people (53,1%) and the again in the elderly category (> 60 years) as many as 30 people (46,9%) and none of the respondents wre in the adolescent category (11-19 yeras). Most of the respondents were female as many as 48 people (75,0%) while 26 while the male sex was 16 people (25,0%) 38 respondents (59,6%) were not obese, while 26 respondents were obese (40,6%). Physical activity of category as many as 26 people (40,6%) modrate physical activity as many 20 people (68,8%). Most of the respondents who smoked wre 23 people (35,9%) and there was a relationship between the risk factors of age, gender, obesity, physical activity, smoking habit with type 2 diabetes melitus.